2014
DOI: 10.1186/1471-2229-14-152
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of rind penetrometer resistance in two maize recombinant inbred line populations

Abstract: BackgroundMaize (Zea Mays L.) is one of the most important cereal crops worldwide and provides food for billions of people. Stalk lodging can greatly undermine the standability of maize plants and therefore decrease crop yields. Rind penetrometer resistance is an effective and reliable method for evaluating maize stalk strength, which is highly correlated with stalk lodging resistance. In this study, two recombinant inbred line populations were constructed from crosses between the H127R and Chang7-2 lines, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 54 publications
7
43
1
Order By: Relevance
“…High marker density is preferable for accurate identification of recombination breakpoints in mapping populations and improvement in the estimates of QTL positions. Advances in sequencing technology have enabled higher marker densities for identification of genetic loci associated with agronomic traits (Jones et al ; Ganal et al ; Tian et al ; Li et al ). Use of GBS and construction of bin maps has proven to be a successful strategy for improved QTL detection in rice (Huang et al ; Xie et al ; Yu et al ) and sorghum (Zou et al ).…”
Section: Discussionmentioning
confidence: 99%
“…High marker density is preferable for accurate identification of recombination breakpoints in mapping populations and improvement in the estimates of QTL positions. Advances in sequencing technology have enabled higher marker densities for identification of genetic loci associated with agronomic traits (Jones et al ; Ganal et al ; Tian et al ; Li et al ). Use of GBS and construction of bin maps has proven to be a successful strategy for improved QTL detection in rice (Huang et al ; Xie et al ; Yu et al ) and sorghum (Zou et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of stalk strength is time-consuming in maize breeding, as exemplified by the decreasing stalk lodging rate from 19.6 to 13.6% within the Iowa Stiff Stalk Synthetic maize population, which required more than 50 years of recurrent selection (Lamkey, 1992). Several genetic studies have revealed that stalk strength is generally controlled by numerous quantitative trait loci (QTLs; Flint-Garcia et al, 2003b;Peiffer et al, 2013;Li et al, 2014). However, the molecular genetic mechanism related to stalk strength in maize remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Though the wind tunnel experiments are useful in intuitively determining the stalk lodging resistance in corn, it has a drawback in that it is unsuitable for on-site quantitative studies [18]. Other laboratory measurements of stalk lodging resistance include hydraulic machinery, such as stalk crushing strength (SCS) and rind penetrometer resistance (RPR), which provides mechanical characteristics of corn stalks [19][20][21][22]. For rapid corn stalk lodging resistance measurements, a stalk hardness meter was developed, and it showed that the stalk strength decreased with planting density increase for the same corn varieties [23,24].…”
Section: Introductionmentioning
confidence: 99%